Proyecto factibilidad para la implementación de una microempresa de procesamiento y comercialización de carne de tilapia empacada al vacío, en la ciudad de Zamora, provincia de Zamora Chinchipe para el año 2016 - Cañar Nantipa, Karina Alexandra (2017)
The project under study was carried out in the city of Zamora, province of Zamora Chinchipe, whose main objective is to carry out a project for the creation of a microcompany for the processing and commercialization of vacuum-packed tilapia meat, which served to determine the feasibility of the Implementation of this project. In addition to being required to opt for the degree of Commercial Engineer. With the development of this research work, the overall objective of the project was achieved, based on the development of specific objectives. With the application of the procedures, it was possible to first determine the theoretical framework selected for the development of the present research study, then selected the materials, methods and techniques for the development of this project, the methodological framework allowed to determine the universe object of study, is Say a portion of the economically active population of the city of Zamora (6,101 inhabitants), to calculate the sample that was 364 inhabitants, where the research tool known as the survey was used, once the survey data were obtained Proceeded to perform the interpretation of the results ie the collection, tabulation and analysis of the investigative instrument, proceeding to carry out the measurement of the supply and demand existing in the city of Zamora, this data provided provided the information necessary to carry out the projection Of investment and determination of fl For the number of years projected, culminated in the economic and financial evaluation through the application of the financial indicators, obtaining the following results: Net Present Value of 91.268.08; An Internal Rate of Return of 41.15%; A Capital Recovery Period of 2 years 6 months and 25 days and a Cost Benefit Ratio of 1.10, determining in this way the favorable feasibility of the project. It was finalized by issuing the respective conclusions and recommendations of the project.